Sistem Ekonomi Kerakyatan Dalam Al-Qur’an Perspektif Tafsir Nusantara - Putri, Melly Septiana; Chozin, Fadjrul Hakam (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2024)
This research was conducted because of the importance of understanding the principles of populist economics, which in recent decades the populist economic system has emerged as an alternative in an effort to achieve inclusive and sustainable economic development. However, this system is often faced with challenges, especially in the context of globalization and economic modernization. A deep understanding of the populist economic system contained in the verses of the Qur'an is very important in facing various economic challenges, such as economic disparities, poverty, social injustice, and others. The problems to be examined in this study are 1) how the interpretation of the economic verses of the people in the interpretation of the archipelago, 2) how the linkage of the economic verses of the people with the economic system of the people. while the purpose of this study is to explain the verses related to the economic system of the people in the interpretation of the archipelago and analyze the interpretation of the economic verses of the people, as well as explain its relationship with the economic system of the people in Indonesia. In answering these problems, this research uses a type of library research, using a descriptive qualitative research model and maudhu'i method. The conclusion of this research is that the Nusantara mufassirs used in this study do not specifically mention and interpret certain verses as a form of populist economy. However, the mufassirs interpret the verses of the Qur'an that contain indicators of a populist economy, namely the command to ta'awun or help in goodness which is implemented by the establishment of cooperatives, management of natural resources for the prosperity of the people, the command to work hard which is characterized by the development of MSMEs as the main driver of the populist economy, and economic equity to reduce economic disparities by ensuring that profits, opportunities, and access to resources are distributed fairly to all people.